Characterization of Mongolian natural minerals and their application for heavy metal adsorbent - D, Munkhbat; Shiomori, K; B, Ochirkhuyag (Mongolian Journal of Chemistry, 2017)
In this study, the structural characteristic and the adsorption properties of heavy metals on Mongolian natural minerals were investigated. The natural samples were confirmed as Heulandite group of Clinoptilolite type zeolite and clay sample that contains albite and quartz by X-ray diffraction analysis. According to BET surface analysis, natural zeolites have mesoporous type of pore. The results of adsorption study showed that adsorption ability of natural zeolite is high effective for lead ion in acidic aqueous solution and the order of heavy metal selectivity was Pb2+>>Zn2+>Cd2+. The adsorption performance of Arsenic(V) is significantly increased by modification with magnesium oxide on natural zeolite.